2014
DOI: 10.1044/2014_lshss-13-0008
|View full text |Cite
|
Sign up to set email alerts
|

Classroom-Based Narrative and Vocabulary Instruction: Results of an Early-Stage, Nonrandomized Comparison Study

Abstract: These preliminary results provide early evidence of the feasibility of implementing a narrative instruction program in a classroom setting. Children at a high risk for language difficulties appeared to profit more from the narrative instruction than from the embedded vocabulary instruction. More extensive research on this instructional program is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…In the case of the vocabulary probe, the pattern was opposite: Although both clinically significant, the posttest gains were much larger for the low-than high-risk experimental groups and not observed in the control groups. The authors argued that classroom-based narrative language with embedded vocabulary instruction can lead to clinically significant change in narrative Gillam et al (2014), Spencer et al (2015) compared a whole class preschool narrative language program implemented in 15-20 minute lessons, 3 times per week for 4 weeks (n ¼ 36) to a business-asusual classroom (n ¼ 35) at a Head Start preschool. Significantly greater gains in the experimental group were found on program-specific outcome measures of narrative recall and story comprehension, but not story generation.…”
Section: Slp-educator Classroom Collaboration: Evidence and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the vocabulary probe, the pattern was opposite: Although both clinically significant, the posttest gains were much larger for the low-than high-risk experimental groups and not observed in the control groups. The authors argued that classroom-based narrative language with embedded vocabulary instruction can lead to clinically significant change in narrative Gillam et al (2014), Spencer et al (2015) compared a whole class preschool narrative language program implemented in 15-20 minute lessons, 3 times per week for 4 weeks (n ¼ 36) to a business-asusual classroom (n ¼ 35) at a Head Start preschool. Significantly greater gains in the experimental group were found on program-specific outcome measures of narrative recall and story comprehension, but not story generation.…”
Section: Slp-educator Classroom Collaboration: Evidence and Discussionmentioning
confidence: 99%
“…Three of the studies addressed narrative language and (Gallagher & Chiat, 2009) comparing direct group intervention (96 hours) and classroom-based services (11 hours) for preschool children was not included in the review due to the highly discrepant difference in hours of service across the treatment conditions. Gillam et al (2014) identified children in two grade 1 classrooms as either high or low risk based on a cut-off standard score of 90 on the Test of Narrative Language (Gillam & Pearson, 2004). For the experimental classroom (low risk: n ¼ 10; high risk: n ¼ 11), the SLP provided 30-minute, full class narrative language instruction sessions targeting story grammar and related vocabulary, elaboration, and independent storytelling 3 times per week for 6 weeks.…”
Section: Slp-educator Classroom Collaboration: Evidence and Discussionmentioning
confidence: 99%
“…It has been studied in groups of three or four students with specific language impairment (SLI) or students who are learning English as a second language and also has been investigated in a classroom context (Gillam, Olszewski, Fargo, & Gillam, 2014) and when provided individually to students with SLI and autism spectrum disorder (ASD; Gillam, Hartzheim, Studenka, Simonsmeier, & Gillam, 2015).…”
Section: Narrative Intervention (Skill)mentioning
confidence: 99%
“…In this sense, the narrative is an important aspect of language, directly relevant for the social and academic development of children (21) . The program involved identification, exploration and production of the narrative elements, using oral support, images and writing (14,22) . Nine weekly meetings were planned, with the materials coherent with the academic level of the sample, selected in partnership with the teachers.…”
Section: ) Drawing Up Of the Programmentioning
confidence: 99%
“…Programs involving oral language practices have shown relevant results in student learning, as they potentialize the development of reading and/or writing (11)(12)(13)(14)(15)(16)(17) . However, we have not found studies on the influence of these programs on the social functioning of Elementary School children.…”
Section: Introductionmentioning
confidence: 99%